2016
DOI: 10.1016/j.optom.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in corneal curvature and its relationship to axial length in the Correction of Myopia Evaluation Trial (COMET) cohort

Abstract: PurposeTo describe longitudinal changes in corneal curvature (CC) and axial length (AL) over 14 years, and to explore the relationship between AL and CC, and the axial length/corneal radius (AL/CR) ratio.MethodsIn total 469, 6 to <12-year-old, children were enrolled in COMET. Measurements of refractive error, CC (D), CR (mm), and ocular component dimensions including AL were gathered annually. Linear mixed models were used to evaluate longitudinal changes adjusting for covariates (gender, ethnicity, lens type,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 40 publications
2
53
0
Order By: Relevance
“…AL/CR RATIO AND RELATIONSHIPS AMONG THE SE AND AL, CR, AND AL/CR RATIO: The distributions of the AL/CR ratio have been reported in different populations and age groups 31,[34][35][36][37][38][39][40][41] and the AL/CR ratios for myopia were between 2.9 and 3.1 and less than 2.9 for emmetropia and hyperopia. 26,27,[42][43][44][45][46] Table 4 summarizes the other studies. In the current report, the CR was approximately the same as that in those previous reports, and women had significantly steeper corneal curvature values, 43 whereas the current AL was longer than those reported previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AL/CR RATIO AND RELATIONSHIPS AMONG THE SE AND AL, CR, AND AL/CR RATIO: The distributions of the AL/CR ratio have been reported in different populations and age groups 31,[34][35][36][37][38][39][40][41] and the AL/CR ratios for myopia were between 2.9 and 3.1 and less than 2.9 for emmetropia and hyperopia. 26,27,[42][43][44][45][46] Table 4 summarizes the other studies. In the current report, the CR was approximately the same as that in those previous reports, and women had significantly steeper corneal curvature values, 43 whereas the current AL was longer than those reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…26,27,[42][43][44][45][46] Table 4 summarizes the other studies. In the current report, the CR was approximately the same as that in those previous reports, and women had significantly steeper corneal curvature values, 43 whereas the current AL was longer than those reported previously. Therefore, the mean AL/CR ratio became the highest.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies indicate that changes in corneal curvature during childhood [36][37][38] and early adulthood [39] are minimal and not associated with the magnitude of myopia progression. However, since the correlation between spherical equivalent refraction (SER) and the axial length to corneal radius ratio is typically stronger than that of axial length alone (by 15-20%) [40][41][42][43], corneal curvature does appear to make a modest contribution to the magnitude of myopia.…”
Section: Corneamentioning
confidence: 99%
“…Ocular biometrics, such as corneal radius (CR) 6 and lens thickness (LT), 7 as well as demographic factors, including age and sex, 8 have been found to be associated with axial length (AL) elongation in childhood. In addition, numerous animal and human studies have revealed a significant association between AL and choroidal thickness.…”
mentioning
confidence: 99%